A critical study of colonial hang-ups in Karim Raslan's Heroes and other stories and Kam Raslan's Confessions of an old boy - Shamin binti Abu Bakar (Kulliyyah of Islamic Reavealed Knowledge and Human Sciences, International Islamic University Malaysia, 2010)
Although this study examines the post-colonial theory, it investigates colonial hang-ups that exist in Malaysia during the colonial days and also in the contemporary society by studying the works of the Raslan brothers and making reference to Franz Fanon's works, particularly the methods he uses to analyse postcolonialism. The findings will be based on library research and interviews with the Raslan brothers to gain additional insights into their perception of postcolonialism .The study will identify the colonial hang-ups of the characters who populate the texts and analyse them in order to give an insight into the Malaysian postcolonial experience. It will be necessary to compare the types of colonial hang-ups that the two brothers write about and explain the similarities and differences. Kam Raslan seems to concentrate on the hang-ups of people who came of age during the colonial era while Karim discusses the hang-ups of contemporary society.